Guidelines for Authors - Žurnalas, Ekonomika (Ekonomika, 2005)
The journal Ekonomika (established and published by Vilnius University) is included in the list of Lithuanian serials that meet the requirements for publications toward the doctoral and habilitation degrees (Department of Science and Higher Education of the Ministry of Education and Science order 01 05 1998 No. 13, confirmed by the Lithuanian Science Council 10 November 1997 decision No. 111-39).